Development of German reading comprehension in two-way immersive primary schools. (June 2022) - Preusler, Sandra; Zitzmann, Steffen; Baumert, Jürgen; Möller, Jens
Abstract: Two-way immersion (TWI) is a variant of the increasingly popular bilingual instruction. Most TWI research lacks longitudinal data or the consideration of background variables to control for possible selection effects. This article examines the development of German reading comprehension of TWI students (N = 984) from fourth to sixth grade compared to conventionally taught students (N = 992). The latent growth curve models showed that immersion students reached the same level of German reading comprehension over the three measurement points, even if background variables like first language, socioeconomic background, and cognitive ability were included. Despite reduced instruction in German, TWI students showed the same reading comprehension level as students in regular instruction while having the advantage of learning an additional language. Although the level of reading comprehension differed between language groups (L1 German speakers, L1 partner language speakers, simultaneous bilinguals), the learning trajectories of reading comprehension were similar. Highlights: TWI students showed comparable reading performance to regular students in Grade 4. L1 partner language speakers performed similarly in both types of school. The results replicate the native language effect. L1 German speakers outperform bilingually raised students in reading in Grade 4. No differences in learning trajectories emerged between TWI and regular students.